2020
DOI: 10.1186/s13052-020-0786-8
|View full text |Cite
|
Sign up to set email alerts
|

Predict respiratory distress syndrome by umbilical cord blood gas analysis in newborns with reassuring Apgar score

Abstract: Background: Neonatal acidaemia at birth can increase neonatal morbidity and mortality and it is predictive of neonatal asphyxia. The umbilical blood gas analysis is a valid tool for the evaluation of neonatal acidaemia. However, umbilical cord blood gas analysis is commonly performed in high-risk situations or in the setting of Apgar scores < 7 at 5 min. Methods: A retrospective cohort study was conducted from June to December 2018 at the Department of mother's and child's health, Poliambulanza Foundation Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
3
16
0
1
Order By: Relevance
“…One study concluded that low blood pH at birth is associated with RDS in newborns and the blood gas analysis is important for early identification of newborns at high risk for RDS, 48 and another study showed that early blood gas analysis may be able to predict RD and both studies were agreed with the results of our study. 14 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One study concluded that low blood pH at birth is associated with RDS in newborns and the blood gas analysis is important for early identification of newborns at high risk for RDS, 48 and another study showed that early blood gas analysis may be able to predict RD and both studies were agreed with the results of our study. 14 …”
Section: Discussionsupporting
confidence: 89%
“…41 In agreement with our results, some studies indicated that the increased OS accompanied by reduced antioxidant defenses may play a significant role in the pathogenesis of RD in preterm newborns 67 and our results agreed with some studies revealed that there was an evidence of oxidative damage and diminished antioxidant defenses in newborns with RDS and the neonatal RDS is associated with certain damage of the cell lipids, proteins and DNA, due to the effect of oxidative stress. 68 One study concluded that low blood pH at birth is associated with RDS in newborns and the blood gas analysis is important for early identification of newborns at high risk for RDS, 48 and another study showed that early blood gas analysis may be able to predict RD and both studies were agreed with the results of our study. 14 In disagreement with our results, some studies stated that cord blood gases did not help in prediction of morbidity in neonates as RDS, and the values of cord blood gas did not predict the presence or severity of RDS, 69 while in agreement with our results, some researches showed that the elevated plasma LDH is strongly related to respiratory system affection in neonates which occur in first days of life especially neonatal RDS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Approximately 25% to 30% of survivors may be at risk of lifelong neurological impairment and disabilities [4]. The efficiency of many current existing methods on HIE diagnosis, such as Apgar series score, cord blood gas, cranial ultrasound, and magnetic resonance imaging (MRI), have proven to be controversial and modest due to individual subjectivity, methodological shortcomings, and the complexity of the encephalopathy [5][6][7][8][9][10][11][12]. For instance, MRI, as one of the main popular diagnostic tools, often shows false-negative results due to its low sensitivity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Immediate identification of respiratory distress syndrome (RDS) and early treatment is important to reach better outcomes. So, it is important to identify early biomarkers of RDS such as blood gas analysis (BGA) to improve diagnosis [ 163 ]. In 352 full term neonates born from vaginal delivery with Apgar score > 7 at 5 minutes, arterial cord BGA results showed an association with RDS, specifically for arterial cord blood pH < 7.12, in 33.8% of infant.…”
Section: Introductionmentioning
confidence: 99%